THE SHAPE OF SOUND: A CONTRASTIVE PHONOLOGICAL STUDY OF MINANGKABAU, SASAK, AND ANGKOLA - Ulil Amri; Alpi Anwar Pulungan; Baiq Annisa Yulfana Nalurita (PROCEEDING OF NATIONAL SEMINAR ON LITERATURE, LINGUISTICS AND LANGUAGE TEACHING, 2026)
Although regional languages in Indonesia are phonologically diverse, few studies have compared these languages directly, especially within the field of contrastive linguistics. This descriptive-contrastive research aims to identify and compare the phoneme inventories of Minangkabau, Angkola, and Sasak languages. The data were obtained from 12 informants across six observation points, two per language. The study employed 417 lexical items derived from 200 Swadesh entries and 217 culturally related lexicons. The results show that Minangkabau has five vowels (/i/, /e/, /a/, /u/, /o/), Sasak has nine vowels (/i/, /e/, /u/, /a/, /o/, /ɪ/, /ɛ/, /ɯ/, /ᴐ/), and Angkola exhibits a more complex vowel system including lax vowels and length contrasts (/i/, /i:/, /ɪ/, /e/, /ɛ/, /a/, /a:/, /ʌ/, /ᴐ/, /ᴐ:/, /o/, /u/, /u:/, /ʊ/, /ɯ/). The consonant distribution is similar across languages, covering bilabial (/p/, /b/, /m/, /w/), alveolar (/t/, /d/, /r/, /n/, /s/, /l/), palatal (/ɲ/, /j/, /ʨ/, /ʥ/), velar (/k/, /g/, /ŋ/), and glottal (/h/, /ɂ/), with the addition of fricatives (/f/, /z/) in Minangkabau and a uvular consonant (/q/) in Sasak. Diphthongal systems differ significantly: /a͡e/, /a͡ɛ/, /a͡y/, /a͡u/, /i͡a/, /u͡ə/, /o͡e/, /o͡ə/ in Sasak, /a͡y/, /a͡e/, /a͡w/, /a͡ᴐ/, /u͡ᴐ/, /u͡ɛ/, /i͡ᴐ/ in Angkola, and /i͡a/, /i͡ə/, /u͡a/, /u͡ə/, /e͡a/, /u͡y/, /o͡y/, /a͡w/, /a͡y/ in Minangkabau. The results show that these languages share a common articulatory base but differ in phonological complexity, especially in vowel and diphthong systems. This research contributes to comparative phonology and regional language documentation.